Tell Tchaikovsky the news rock 'n' roll, the labor question, and the musicians' union, 1942-1968 - Roberts, Michael James 1967- (Duke University Press, 2014)
Solidarity forever? : the musicians' union responds to records and radio -- Have you heard the news? : there's good rockin' tonight : hepcats, wildcats and the birth of rock 'n' roll -- If I had a hammer : union musicians "bop", rhythm and blues, and rock 'n' roll -- A working-class hero is something to be : the musicians' union attempt to block the British invasion -- Tuned in, turned on, and dropped out : rock 'n' roll music production restructures the music industry -- Along nonunion lines